Environmental assessment of nitrogen compounds in the surroundings of a fertilizers industrial plant - CHIOREAN, Florin Ștefan; ROBA, Carmen Andreea; BIZĂU-CÂRSTEA, Maria Lucia (Studia Universitatis Babeș-Bolyai Ambientum, 2023)
The present study was conducted in the proximity of a chemical plant from Târgu-Mureș (Romania), where nitrogen-based fertilizers were produced. The quality of the environmental components was assessed in terms of general physico-chemical parameters and the content of nitrogen dissolved ions (NO3-, NO2-). The nitrate content in soil varied depending on the distance from the source and land use at sampling point. The nitrite content was correlated with possible transformations from the nitrate forms. For water, special attention should be paid to the nitrate content from the industrial effluent, which in one sample proved to be higher than the national legislation.